SERPINA1 Gene Promoter Is Differentially Methylated in Peripheral Blood Mononuclear Cells of Pregnant Women - Rotondo, John Charles; Oton-Gonzalez, Lucia; Selvatici, Rita; Rizzo, Paola; Pavasini, Rita; Campo, Gianluca Calogero; Lanzillotti, Carmen; Mazziotta, Chiara; De Mattei, Monica; Tognon, Mauro; Martini, Fernanda (Frontiers in Cell and Developmental Biology, 2020)
SERine Protein INhibitor-A1 (SERPINA1) is an inducible blood cell gene coding for alpha1-antitrypsin (AAT), a plasma protease inhibitor whose circulating levels are raised during inflammation, infection and advanced pregnancy. DNA methylation has been suggested to play a role in SERPINA1 gene expression regulation in peripheral blood mononuclear cells (PBMCs). The methylation status of SERPINA1 in PBMCs is unknown. The aim of this study was to evaluate the methylation profile of the SERPINA1 promoter in PBMC. To this purpose PBMCs and serum were collected from healthy subjects (HS) (n=75), including blood donors (BD) (n=25), pregnant women at early pregnancy (EP) (n=25), i.e. within the first trimester, and pregnant women at late pregnancy (LP) (n=25), i.e. at the third trimester. DNA from PBMCs was treated with sodium bisulfite and PCR amplified for SERPINA1 gene promoter, followed by sequencing analyses. AAT serum levels were determined by E.L.I.S.A. test. SERPINA1 was found hypermethylated in 58.7% of HS. The prevalence of SERPINA1 hypermethylation was significantly higher in BD (68%) and EP (88%) than in LP (20%) (p<0.01). The median serum AAT concentration was 1.07, 0.63 and 3.15 mg/ml in BD, EP and LP, respectively (p<0.05, BD and EP vs LP). This study indicates, for the first time, that SERPINA1 gene promoter is differentially methylated in PBMCs from HS. Likely, modulation of the methylation may be a novel epigenetic regulator mechanism of AAT expression in the PBMC of HS. Therefore, SERPINA1 gene promoter methylation may represent an epigenetic biomarker of PBMCs in healthy subjects.